1997
DOI: 10.1097/00005392-199703000-00049
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Complications of Salvage Cryotherapy of the Prostate

Abstract: Salvage cryotherapy impacts local tumor control as evident by the high frequency of negative posttreatment biopsies. A double freeze-thaw cycle appears more effective than a single cycle. Like salvage prostatectomy, salvage cryotherapy causes significant morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 13 publications
1
30
1
3
Order By: Relevance
“…After radiotherapy rectourethral fistula formation was seen in up to 10% of patients [22], but it did not lead to more incontinence in this series. This is in contrast with Pisters et al [30]who observed an incontinence rate of almost 80% after radiotherapy.…”
Section: Cryosurgical Ablation Of the Prostatecontrasting
confidence: 81%
See 1 more Smart Citation
“…After radiotherapy rectourethral fistula formation was seen in up to 10% of patients [22], but it did not lead to more incontinence in this series. This is in contrast with Pisters et al [30]who observed an incontinence rate of almost 80% after radiotherapy.…”
Section: Cryosurgical Ablation Of the Prostatecontrasting
confidence: 81%
“…Pisters et al [30]reported on a series of patients treated with CSAP with local failure, 110 after radiotherapy alone and 40 after a combination of androgen deprivation and radiotherapy. In the 'radiotherapy alone’ group after 1–2 CSAP sessions a negative biopsy result could be obtained in 95% of patients compared with a 75% negative biopsy results in the 'radiotherapy and androgen deprivation’ group.…”
Section: Cryosurgical Ablation Of the Prostatementioning
confidence: 99%
“…Therapeutische Alternativen zur SR-PE bestehen in der Kryotherapie [5,11,14,32] und der interstitiellen Brachytherapie [6,20]. Die bisher beschriebenen funktionellen und onkologischen Resultate der Kryotherapie mit Geräten der 1. und 2.…”
Section: Komplikationsratenunclassified
“…Reported postsalvage cryosurgery UI rates range from 0% to 83% 62, 63, 64, 65, 66, 67. Generally, men treated with cryotherapy report higher prevalence of urinary symptoms compared with RP in the short term, but the symptoms improve or disappear after ≥ 3 months 68, 69.…”
Section: Introductionmentioning
confidence: 99%